2017
DOI: 10.1680/jsmic.17.00001
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian monitoring techniques for crowd-flow prediction

Abstract: The high concentration and flow rate of people in train stations during rush hours can pose a prominent risk to passenger safety and comfort. In situ counting systems are a critical element for predicting pedestrian flows in real time, and their capabilities must be rigorously tested in live environments. The focus of this paper is on evaluating the reliability of two alternative counting systems, the first using an array of infrared depth sensors and the second a visible light (RGB) camera. Both proposed syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In past, large numbers of people died due to suffocation in crowded areas in various public gathering events. Better crowd management can be made in such events to avoid accidents [ 29 , 30 , 31 ].…”
Section: Applicationsmentioning
confidence: 99%
“…In past, large numbers of people died due to suffocation in crowded areas in various public gathering events. Better crowd management can be made in such events to avoid accidents [ 29 , 30 , 31 ].…”
Section: Applicationsmentioning
confidence: 99%
“…In the recent past, huge numbers of people have died from suffocation in highly crowded areas in different public-gathering events. Early detection of overcrowding and better crowd management in political rallies, sports events, and musical concerts can be made possible by analyzing the crowd gathering [129][130][131].…”
Section: Applications Of Cnn-cc Algorithmsmentioning
confidence: 99%
“…Based on the extracted features, the model was designed to select the optimal route for the passengers' target station. In a comparative study on two pedestrian monitoring techniques to predict crowd flow, Martani et al [47] compared an array of infrared depth sensors and a visible light (RGB) camera. Their findings revealed that the developed RGB-based system performed reliably across a wide range of conditions, while the former approach was demonstrated to be a useful supplement in conditions without significant ambient sunlight, such as underground passageways.…”
Section: Crowd Spatio-temporal Analysismentioning
confidence: 99%